2020
DOI: 10.1037/men0000252
|View full text |Cite
|
Sign up to set email alerts
|

Linking alcohol-specific masculine norms and drinking behavior among Latino men.

Abstract: A robust literature suggests men typically engage in more general and heavy alcohol use than women, and that many health disparities related to drinking are more prevalent among Latino men compared with non-Latino White men. Researchers posit that adherence to masculine gender role scripts may be one reason men choose to drink alcohol. To date, research linking masculinity to drinking among Latinos has been mixed and has used broad measures for masculinity that are arguably quite distal from alcohol outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…These risky, health-related behaviors include binge drinking and substance abuse (e.g. Liu and Iwamoto, 2007; Peralta, 2007; Perrotte et al, 2020), risky sexual practices (e.g. Mahalik et al, 2006; Parmenter et al, 2020), physical fighting (e.g.…”
Section: Hm and Healthmentioning
confidence: 99%
“…These risky, health-related behaviors include binge drinking and substance abuse (e.g. Liu and Iwamoto, 2007; Peralta, 2007; Perrotte et al, 2020), risky sexual practices (e.g. Mahalik et al, 2006; Parmenter et al, 2020), physical fighting (e.g.…”
Section: Hm and Healthmentioning
confidence: 99%
“…To advance researchers’ and practitioners’ understanding of masculine norms and their associations with alcohol use, Perrotte et al (2020) created the Masculine Drinking Norms Measure (MDNM). The MDNM was adapted from the Traditional Machismo and Caballerismo Scale (TMCS; Arciniega et al, 2008).…”
Section: Study Aimsmentioning
confidence: 99%
“…However, unlike the CMNI, the TMCS also measures caballerismo , which is considered to be a more adaptive dimension of masculinity and is characterized by traits such as respect, nurturance, and polite etiquette. Perrotte et al (2020) relied on the concept underlying the TMCS to measure how norms around drinking for men can be maladaptive (i.e., through excessive drinking) or adaptive (i.e., through exerting behavioral control while drinking). These gender role scripts align with Klein’s (1992) early work with college students which indicated that compared to women, men reported higher levels of agreement with the statement that “a real man should be able to hold his liquor” than women.…”
Section: Study Aimsmentioning
confidence: 99%
“…Recent work also found that immigration‐related stress exerted a stronger influence on alcohol use severity among men than women (Cano et al., 2017). A common explanation is that gender social norms, including among Latinos (Perrotte et al., 2020), influence differences in gender‐specific alcohol use such that drinking alcohol is often normalized and reinforced among men but considered inappropriate for many women (Kulis et al., 2012). In addition to gender, time spent in U.S. residency correlates with increased alcohol use among Latino immigrant populations (Martinez et al., 2011; Salas‐Wright et al., 2014).…”
Section: Alcohol Trajectories During Adolescencementioning
confidence: 99%